Interaction between an Eco-Spiral Bolt and Crushed Rock in a Borehole Evaluated by Pull-Out Testing - Seong-Seung Kang; Atsuo Hirata; Bo-An Jang; Yong-Seok Seo; Daehyeon Kim (Advances in Materials Science and Engineering)
The interactions between an eco-spiral bolt and crushed rocks in a borehole were evaluated by pull-out testing in a laboratory and numerical analysis. The porosity of the crushed rock surrounding the bolt depended on the size of the eco-spiral bolt and affected the eco-spiral bolt’s axial resistance force. The axial resistance force and the porosity of the crushed rocks in the borehole showed an inverse relationship. The porosity was also related to the size of the eco-spiral bolt. The maximum principal stress between the bolt and the rock was related to the porosity of the crushed rock and the size difference between the eco-spiral bolt and the borehole. At low porosity the experimental and numerical analyses show similar relationships between the axial resistance force and the displacement. However, at high porosity, the numerical results deviated greatly from the experimental observation. The initial agreement is attributed to the state of residual resistance after the maximum axial resistance force, and the latter divergence was due to the decreasing axial resistance force owing to slippage.